(untitled) (Modern education and development, 2025)
This article explores the impact of folk remedies on children’s diseases, focusing on their psychological effects. Traditional healing methods, including herbal medicine, aromatherapy, and music therapy, play a crucial role in supporting children’s mental and emotional well-being. The paper reviews various studies and presents findings that highlight the effectiveness of these remedies in complementing modern medicine. Additionally, the study discusses the historical context of folk remedies and their relevance in contemporary healthcare practices.